Theoretical analysis of guided waves propagation in periodic piezoelectric plates with shunting circuits - Zhang, Youqi; Xia, Rongyu; Huang, Kefu; Li, Zheng (Frontiers in Physics, 2022)
The tunable manipulation of guided waves in plates brings out great potential applications in engineering practices, and the electromechanical coupling effects of piezoelectric material with shunting circuits have exhibited powerful tunability and flexibility for guided wave propagation. In this paper, a theoretical model is established to analyze the guided wave propagation in one-dimensional periodic piezoelectric plate constructed from a periodic array of anisotropic piezoelectric materials under periodic electrical boundary conditions. The extended Stroh formalism incorporating with the plane wave expansion method is developed to transform the wave motion equations of the periodic piezoelectric plate into a linear eigenvalue system, and a more concise and elegant solution of generalized displacement and generalized stress can be derived. There are various dispersion relations in terms of the altering electrical boundary conditions to be acquired, if the thin electrodes with shunting circuits are attached periodically to both surfaces of the piezoelectric plate. Analytical results show that the coupling of the local electric resonant mode and propagating elastic wave modes can induce hybridization bandgaps, and the bandgaps of Lamb waves and SH waves in the piezoelectric plate can be tuned by designing appropriate material polarization orientations and shunting circuits. In addition, the Bragg bandgaps can also be influenced by the external circuits. Results indicate that the proposed theoretical model can effectively analyze the performances of guided waves in periodic piezoelectric plate and provide useful theoretical guidance for designing smart wave control devices.